Effect of salinity on supercritical CO2 permeability of caprock in deep saline aquifers: An experimental study. (15th January 2020) - Jayasekara, D.W.; Ranjith, P.G.; Wanniarachchi, W.A.M.; Rathnaweera, T.D.; Chaudhuri, A.
Abstract: The permanence of injected CO2 in deep saline aquifers mainly depends on caprock permeability. Thus, the main objective of this study is to investigate the effect of salinity level in the formation fluid on permeability of siltstone when advective flow of scCO2 is dominant. Siltstone caprock samples were fully saturated with different synthetic brines, which were similar to natural formation fluids. A chemical analysis was conducted for each saturated rock and brine samples to recognize the geo-chemical equilibrium between the formation fluid and caprock since the identification of final brine composition in rock pores is crucial to predict the possible interactions with scCO2 flow. Interestingly, the results show that the caprock is subjected to dissolution during saturation due to ion exchange between caprock minerals and cations in the pore fluid changing the brine elemental composition. The scCO2 permeability experiments were conducted for each saturated sample using a core flooding apparatus for a series of injection pressures. According to the results, scCO2 permeability significantly reduces at high salinity concentrations in brine due to deposition of different types of evaporites in rock pores which significantly depends on the elemental concentration of brine and caprock-brine interaction. It is known as CO2 dry-out phenomenon. Highlights: Chemical analysis and scCO2 flow tests were conducted for brine saturated caprock. Accordingly, brine composition changes as cations in brine exchange with caprock. ScCO2 permeability significantly reduces at high salinity concentrations in brine. It's because of subflorescence phenomenon that occurs due to CO2 dry-out effect. Evaporite precipitations depend on brine composition and mineral-brine interaction.